Dietary Behaviors among Patients with Type 2 Diabetes Mellitus in Yogyakarta, Indonesia - Primanda, Yanuar; Kritpracha, Charuwan; Thaniwattananon, Ploenpit (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2011)
Purpose: To describe dietary behaviors and examine relationships between selected factors and dietary behaviors among type 2 diabetes mellitus (T2DM) patients in Yogyakarta, Indonesia.Method: Seventy T2DM patients from a hospital in Yogyakarta who met the inclusion criteria were recruited. Patient’s dietary behaviors were measured by the Dietary Behaviors Questionnaire developed for this study with adequate reliability. The questionnaire comprised of four dimensions: recognizing the amount of calorie needs, selecting healthy diet, arranging a meal plan, and managing dietary behaviors challenges. Higher scores indicate better dietary behaviors.Result: More than half of the patients were women (54.3%) with an average age of 56.8 years and diabetes duration of 9.7 years. The results revealed a moderate level of the total score of dietary behaviors. Considering each dimension, the results showed a moderate level of recognizing the amount of calorie needs, selecting healthy diet, and managing dietary behaviors challenges. The patients reported a high level of arranging meal plans. Pearson’s correlation was used to examine the relationships between selected factors and dietary behaviors. There was a positive significant relationship between the knowledge regarding diabetic diet and the total dietary behaviors scores (r = .36, p< .01). There were positive significant relationships between the knowledge regarding diabetic diet and the dimensions of recognizing the amount of calorie needs (r = .27, p< .05), selecting healthy diet (r = .35, p< .01), and managing dietary behaviors challenges (r = .28, p< .05). In contrast, the findings indicated no significant relationship between knowledge regarding diabetic diet and arranging a meal plan dimension. Furthermore, there was no significant relationship between the diabetes duration and dietary behaviors.Conclusion: Dietary behaviors among T2DM patients in Yogyakarta were at a moderate level. Knowledge regarding diabetic diet is essential. Further study regarding intervention in increasing patients’ knowledge is needed to achieve better dietary behaviors.Keywords: Dietary behaviors, type 2 diabetes mellitus, knowledge, Yogyakarta, Indonesia